MicroFEA 1.0—A software package for Finite Element Analysis of functionally graded materials - Medeiros Júnior, Marcelo Silva (2021)
Functionally Graded Materials (FGM) are a class of advanced composites with a gradual and continuously varying microstructural composition. This paper presents MicroFEA 1.0, which is a software package developed to help overcoming the challenges of designing and analyzing FGM structures. It provides capabilities to fit FGM experimental data to B-Spline curves and to analyze composite materials using mean-field micromechanics homogenization techniques. The package is composed of MATLAB scripts and Fortran subroutines intended for Finite Element Analysis (FEA) using Abaqus. The Abaqus user-material subroutines (UMATs) are designed to work with heterogeneous materials at the integration points level, discarding the need for custom-designed elements. Thermomechanical analyses can also be carried out with the help of UTEMPs. This software will provide valuable help for scientists and engineers facing the development of new FGM structural components.